Utilisation and dynamics of an arid savanna woodland in the Northern Province, South Africa - Rathogwa, Nkhweleleni Ronald (Centre for Statistics in Ecology, the Environment and Conservation, 2023)
This thesis reports upon the findings of a study into the socioeconomic and ecological drivers of plant resource utilisation, and dynamics of woody plants used by rural people in the Northern Province, South Africa. The key components were to (1) quantify the range of socioeconomic drivers of plant resource utilisation in rural communities, (2) identify plant species highly preferred by people and their uses, (3) quantify the impacts of plant resource harvesting, (4) seek relationships between spatial distribution patterns of plants and productivity, (5) determine the responses of trees to harvesting regimes, and (6) elucidate the impacts of selected management actions on plant resource supply and hence sustainability. Each of these was pursued through a combination of surveys and empirical experimentation. High unemployment rate, low educational levels, large family sizes and most importantly low overall family income are characteristic of this rural community. As a result, many people are still reliant on wild growing plants for their household and economic needs. The three main use categories associated with people in this rural village, in order of their importance, are: construction, food and energy. It is construction and energy uses that are associated with very few species. Harvesting of plant materials for these two use categories is destroying the preferred species in communal land. Two plant species, Colophospermum mopane and Androstachys johnsonii, are the most preferred plant species for construction and energy purposes. In a protected area the C. mopane population is stable, an indication that recruitment balances mortality. The same applies to A johnsonii. However, in communal land the size class frequency distribution of C. mopane varies at three distances from the village, suggesting that communal patterns of C. mopane utilisation are unfavourable to this species. This is probably so because of intense browsing within the village and high levels of harvesting. However, A johnsonii at two harvest zones in communal land show the same trend as in the protected area: the inverse J-shaped curve which is a characteristic feature of a stable population. Selective harvesting therefore, has little impact on recruitment of young A. johnsonii trees. Conflicting results were evident with respect to the role of competition in tree populations. Spatial distribution methods (i.e. nearest-neighbour analysis and departure from randomness approach) from a number of plots suggested that competition was not important at most plots. Yet, the strong negative relationship between loge mean stand basal area and log0 stand density indicated that competition is a significant factor affecting individual tree and stand woody productivity. Most plots from the communal land, when plotted on the same graph of plots from the protected site, lay far below the thinning line, suggesting that harvesting is promoting rapid growth of trees in communal land. The five species harvested responded differently from each other. Full and partial harvesting of C. mopane trees during December at ~30 cm above ground level resulted in 100% survival rate after one year. The equivalent diameter of coppice shoots was significantly positively related to stump size and light availability. The former suggests that harvesting bigger trees will result in rapid diameter growth of coppice shoots while the latter suggests that shoots are suppressed by shade from neighbouring trees. The equivalent shoot diameter was significantly negatively related to sum of neighbour size divided distance ratios, an indication of competition between neighbouring trees. All big trees and 70% of the small trees of A johnsonii species died when the same season, height of cutting and harvesting regime applied to C. mopane was used. Partial harvesting resulted in 60 and 45% survival rates for big and small trees respectively. Coppice shoot production of the surviving stems was also very low compared to C. mopane. A static transition model was developed to simulate requirements for sustainable harvesting of Colophospermum mopane woodlands. The model predicts that a combination of high levels of harvesting and browsing will result in the depletion of the resource base within three decades.